2009
DOI: 10.1007/s00296-009-1060-y
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of distal extremity swelling with pitting oedema in psoriatic arthritis: the different pathological mechanisms

Abstract: In psoriatic arthritis, swelling and pitting oedema may be caused by diVerent pathogenic mechanisms: on one hand, the involvement of tenosynovial structures; on the other hand, the involvement of lymphatic vessels, which may be rarely implicated by the inXammatory process. This diVerent involvement is responsible for a diVerent response to therapy and a diVerent clinical outcome. In fact, patients with inXammation of the tenosynovial structures and normal lymphatic drainage have a more favourable clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The first mechanism is tenosynovial involvement, which has been reported only in a few cases. In the study of Quarta et al (6), the cause of edema was reported to be tenosynovial involvement in a case with normal lymph flow. Similarly, Salvarani et al (7) claimed that edema in their patient might have resulted from tenosynovial involvement.…”
Section: Discussionmentioning
confidence: 95%
“…The first mechanism is tenosynovial involvement, which has been reported only in a few cases. In the study of Quarta et al (6), the cause of edema was reported to be tenosynovial involvement in a case with normal lymph flow. Similarly, Salvarani et al (7) claimed that edema in their patient might have resulted from tenosynovial involvement.…”
Section: Discussionmentioning
confidence: 95%
“…Using lymphoscintigraphy and MRI, the researchers differentiated two distinct causes of extremity distention: i) tenosynovial inflammation and ii) lymphatic vessel dysfunction. 6 The authors suggested that patients with tenosynovial involvement without lymphatic changes had a more favorable outcome to teatment. In our patient, who showed no response to standard treatment options, lymphatic involvement may explain her poor outcome to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients' arthritis symptoms benefited from treatment, but there was no improvement in lymphedema. 6 Lepka et al reported a patient with PsA and related left upper arm swelling who was successfully treated with etanercept therapy. 9 Our patient's lymphedema did not improve significantly after DMARD therapy.…”
Section: Recommendations For Evaluationmentioning
confidence: 99%
“…According to our review of the literature, there have been two case reports of remitting distal extremity swelling with pitting oedema in PsA caused by tenosynovitis and one case with RS3PE as the first manifestation of psoriasis (4)(5)(6). Unlike the two case reports, we did not add oral corticosteroid to therapy of our case because of potential rebound of psoriasis.…”
mentioning
confidence: 92%
“…Lymphoscintigraphy and magnetic resonance imaging (MRI) are useful in evaluation. RS3PE responds well whereas lymphoedema resists therapy (4,5).…”
mentioning
confidence: 98%